Is Telephysiotherapy an Option for Improved Quality of Life in Patients with Osteoarthritis of the Knee? - Adesola C. Odole; Oluwatobi D. Ojo (International Journal of Telemedicine and Applications)
This study investigated effect of a 6-week telephysiotherapy programme on quality of life (QoL) of patients with knee osteoarthritis (OA). Fifty patients with knee OA were randomly and equally assigned into two treatment groups: clinic group (CG) and telephysiotherapy group (TG). The CG received physiotherapist-administered osteoarthritis-specific exercises in the clinic thrice weekly for 6 weeks while the TG received structured telephone monitoring with self-administered osteoarthritis-specific exercises for the same duration at home. Participants’ QoL was assessed using WHOQoL-Bref at baseline, second, fourth, and sixth week of intervention. Data were analyzed using ANOVA and independent Student’s t-test. Within-group comparison showed significant improvements in physical health domain (P=0.00* for TG and CG) and psychological domain (P=0.02* for TG; P=0.00* for CG) of WHOQoL following six-week intervention. However, there were no significant differences (P>0.05) in TG and CG’s social relationship and environment domains. Between-group comparison showed no significant differences (P>0.05) between CG and TG’s physical health, psychological, and social relationships domains of WHOQoL following 6-week intervention. However, there was significant difference in the environment domain (P<0.05). Telephysiotherapy using telephone medium improved QoL in patients with knee OA comparable to clinic based treatment.